7 - Nietzsche l’islam et la globalisation - Sanekli Monia, (African Sociological Review, 2014)
“Arab Spring”, or the revolutions of the century broke out with a suction underdeveloped world has freedom, modernity and democracy. The facts lead us to a total diversion goals of the “Arab Spring.” : Obscurantism, Islam, jihad, theocracy dominate . The century in fact expresses a new concept of postmodern revolutions or the society is in intersection between philosophy, politics and religion. The three pillars of all social facts.